The Representation of Cultural Content In ELT Textbook for Middle School Students - Linda Septiyana; Ahmad Subhan Roza; Lydia Hardijanti; Agnira Rekha (Metathesis: Journal of English Language, Literature, and Teaching, 2022)
The research aims to (1) identify the cultural materials in ELT textbooks for middle school students; (2) analyze cultural elements that are presented in ELT textbooks. This English textbook entitle English on Sky was written by Mukarto, Widya Kiswara, Sujatmiko Bambang Santoso, and Josephine Sri Murwani. In this research, the researchers used qualitative methods with analysis techniques. In data collection, the researchers used documentation technique with the steps were 1) reading textbook; 2) identifying cultural content in the textbook as well as checking them based on the theory of Cortazzi and Jin; 3) classifying cultural-based content; 4) encoding the data and 5) interpreting data. The result showed that there were 72 cultural contents that exist in the ELT textbook from chapter one until thirteen. Based on the types of cultural contents including: 46 items of source cultures, 14 items of target cultures, and 12 items of international cultures. The elements of culture presented in this study are product, person, and practice. Elements of the product appeared 54 items, person 9 items, and practice 9 items. Therefore, the ELT textbook entitle English on Sky is very recommended and helpful for middle schools students to enhance their language skills, as well as improve their knowledge about culture.